Whole-genome re-sequencing, diversity analysis, and stress-resistance analysis of 77 grape rootstock genotypes - Wang, Peipei; Zhao, Fanggui; Zheng, Ting; Liu, Zhongjie; Ji, Xinglong; Zhang, Zhichang; Pervaiz, Tariq; Shangguan, Lingfei; Fang, Jinggui (Frontiers in Plant Science, 2023)
Introduction Grape rootstocks play critical role in the development of the grape industry over the globe for their higher adaptability to various environments, and the evaluation of their genetic diversity among grape genotypes is necessary to the conservation and utility of genotypes. Methods To analyze the genetic diversity of grape rootstocks for a better understanding multiple resistance traits, whole-genome re-sequencing of 77 common grape rootstock germplasms was conducted in the present study. Results About 645 billion genome sequencing data were generated from the 77 grape rootstocks at an average depth of ~15.5×, based on which the phylogenic clusters were generated and the domestication of grapevine rootstocks was explored. The results indicated that the 77 rootstocks originated from five ancestral components. Through phylogenetic, principal components, and identity-by-descent (IBD) analyses, these 77 grape rootstocks were assembled into ten groups. It is noticed that the wild resources of V. amurensis and V. davidii, originating from China and being generally considered to have stronger resistance against biotic and abiotic stresses, were sub-divided from the other populations. Further analysis indicated that a high level of linkage disequilibrium was found among the 77 rootstock genotypes, and a total of 2,805,889 single nucleotide polymorphisms (SNPs) were excavated, GWAS analysis among the grape rootstocks located 631, 13, 9, 2, 810, and 44 SNP loci that were responsible to resistances to phylloxera, root-knot nematodes, salt, drought, cold and waterlogging traits. Discussion This study generated a significant amount of genomic data from grape rootstocks, thus providing a theoretical basis for further research on the resistance mechanism of grape rootstocks and the breeding of resistant varieties. These findings also reveal that China originated V. amurensis and V. davidii could broaden the genetic background of grapevine rootstocks and be important germplasm used in breeding high stress-resistant grapevine rootstocks.